New Concepts, Experimental Approaches, and Dereplication Strategies for the Discovery of Novel Phytoestrogens from Natural Sources - Michel, Thomas; Halabalaki, Maria; Skaltsounis, Alexios-Leandros (Planta Medica, 2013)
Phytoestrogens constitute an attractive research topic due to their estrogenic profile and their biological involvement in womanʼs health. Therefore, numerous studies are currently performed in natural products chemistry area aiming at the discovery of novel phytoestrogens. The main classes of phytoestrogens are flavonoids (flavonols, flavanones), isoflavonoids (isoflavones, coumestans), lignans, stilbenoids as well as miscellaneous chemical groups abundant in several edible and/or medicinal plants, belonging mostly to the Leguminosae family. As for other bioactives, the detection of new structures and more potent plant-derived phytoestrogens typically follows the general approaches currently available in the natural product discovery process. Plant-based approaches selected from traditional medicine knowledge and bioguided concepts are routinely employed. However, these approaches are associated with serious disadvantages such as time-consuming, repeated, and labor intensive processes as well as lack of specificity and reproducibility. In recent years, the natural products chemistry became more technology-driven, and several different strategies have been developed. Structure-oriented procedures and miniaturized approaches employing advanced hyphenated analytical platforms have recently emerged. They facilitate significantly not only the discovery of novel phytoestrogens but also the dereplication procedure leading to the anticipation of major drawbacks in natural products discovery. In this review, apart from the traditional concepts followed in phytochemistry for the discovery of novel biologically active compounds, recent applications in the field of extraction, analysis, fractionation, and identification of phytoestrogens will be discussed. Moreover, specific methodologies combining identification of actives and biological evaluation in parallel, such as liquid chromatography-biochemical detection, frontal affinity chromatography-mass spectrometry and pulsed ultrafiltration-MS will also be presented. Finally, miniaturized methods (microchip and biosensor) will be also discussed.With the current review, we attempt to give a wide and holistic overview of the different approaches which could be employed in the discovery of new phytoestrogens. On the other hand, we anticipate to attract more scientists to the area of phytoestrogens and to indicate the need of multidisciplinary concepts.
Keywords: phytoestrogens; plant extract; dereplication; extraction; isolation; identification